The Trypanosoma cruzi vitamin C dependent peroxidase confers protection against oxidative stress but is not a determinant of virulence. - Martin C Taylor; Michael D Lewis; Amanda Fortes Francisco; Shane R Wilkinson; John M Kelly (Public Library of Science (PLoS), 2015)
BACKGROUND:The neglected parasitic infection Chagas disease is rapidly becoming a globalised public health issue due to migration. There are only two anti-parasitic drugs available to treat this disease, benznidazole and nifurtimox. Thus it is important to identify and validate new drug targets in Trypanosoma cruzi, the causative agent. T. cruzi expresses an ER-localised ascorbate-dependent peroxidase (TcAPx). This parasite-specific enzyme has attracted interest from the perspective of targeted chemotherapy. METHODOLOGY/PRINCIPAL FINDINGS:To assess the importance of TcAPx in protecting T. cruzi from oxidative stress and to determine if it is essential for virulence, we generated null mutants by targeted gene disruption. Loss of activity was associated with increased sensitivity to exogenous hydrogen peroxide, but had no effect on susceptibility to the front-line Chagas disease drug benznidazole. This suggests that increased oxidative stress in the ER does not play a significant role in its mechanism of action. Homozygous knockouts could proceed through the entire life-cycle in vitro, although they exhibited a significant decrease in their ability to infect mammalian cells. To investigate virulence, we exploited a highly sensitive bioluminescence imaging system which allows parasites to be monitored in real-time in the chronic stage of murine infections. This showed that depletion of enzyme activity had no effect on T. cruzi replication, dissemination or tissue tropism in vivo. CONCLUSIONS/SIGNIFICANCE:TcAPx is not essential for parasite viability within the mammalian host, does not have a significant role in establishment or maintenance of chronic infections, and should therefore not be considered a priority for drug design.